2019
DOI: 10.1371/journal.pone.0222238
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community composition of biofilms in milking machines of two dairy farms assessed by a combination of culture-dependent and –independent methods

Abstract: Dairy biofilms as a source of contamination of milk and its products are of great concern in the dairy industry. For a reliable risk assessment, knowledge about the microbial community composition of biofilms in the milking systems of dairy farms must be improved. In this work, swab samples of milking machine biofilms of two dairy farms were investigated by a combination of culture-dependent and -independent methods. Spots in the milking system with enhanced microbial colonization were identified by quantifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 62 publications
1
45
0
3
Order By: Relevance
“…As biofilms show increased resistance to mechanical, physsical, and chemical treatments, in comparison to their planktonic state [ 7 ], it is crucial to select suitable sanitation methods [ 8 ]. It is vital to understand that the embedded extracellular matrix of persistent biofilms can protect present potential pathogens and spoilage microorganisms from disinfection treatments [ 9 ]. Any persistent microorganism with the ability to form biofilms can lead to human diseases or alteration in sensory characteristics [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As biofilms show increased resistance to mechanical, physsical, and chemical treatments, in comparison to their planktonic state [ 7 ], it is crucial to select suitable sanitation methods [ 8 ]. It is vital to understand that the embedded extracellular matrix of persistent biofilms can protect present potential pathogens and spoilage microorganisms from disinfection treatments [ 9 ]. Any persistent microorganism with the ability to form biofilms can lead to human diseases or alteration in sensory characteristics [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides staphylococci, Microbacterium spp. were previously isolated from dairy, egg, ready-to-eat, and meat-producing industries [ 9 , 19 , 20 ], among which M. lacticum is abundant on food contact surfaces in dairy-related facilities [ 9 , 19 ]. Microbacterium spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also observed that some of these bacterial species were resistant to certain types of disinfectants [55], which implies that robust, well-validated hygiene regimes should be used for cleaning food processing environments. Weber et al [56] studied the bacterial composition of biofilms in bovine milk and found that Firmicutes, Proteobacteria, Actinobacteria, and Bacteroidetes were the dominant phyla. In the phylum Actinobacteria, Rhodococcus, Dermacoccus, Gordonia, Kocuria and Microbacterium were the main genera.…”
Section: The Biofilm-forming Capability Of the Isolated Bacterial Strmentioning
confidence: 99%
“…However, it has been shown that from the time of contamination until the end of the shelf life of microfiltered milk, Microbacterium's proteolytic and lipolytic activities are below the threshold of detection (Schmidt et al, 2012). Regarding dairy products, it is interesting to note that strains of the genus Microbacterium are often found on the rind of smear-ripened cheeses (Mounier et al, 2005(Mounier et al, , 2007 and that the community of psychrophilic bacteria in raw milk, including Microbacterium, has the ability to form biofilms along the whole milk chain (e.g., on the collection and storage equipment), which poses a risk to the stability of the milk (Weber et al, 2019). However, no data are available on the genomic structures underlying the phenotypes of the genus Microbacterium that are involved in the preservation of extended shelf-life (ESL) milk.…”
Section: Introductionmentioning
confidence: 99%